2008
DOI: 10.4049/jimmunol.180.11.7706
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Depletion Inhibits Spontaneous Autoimmune Thyroiditis in NOD.H-2h4 Mice

Abstract: All NOD.H‐2h4 wild type (WT) mice given NaI water develop SAT, but B cell‐deficient (B−/−) mice are resistant. B cells presumably function as APC for activation of CD4+ T cells. B −/− mice develop SAT comparable to WT mice after transient depletion of T reg, suggesting T reg are preferentially activated if autoantigen is presented by non‐B cells. Anti‐CD20 or isotype control was given to young (1–2 wk) or adult (7 wk) WT mice; all mice were given NaI water at 8 wk, and SAT was evaluated 8 wk later. WT mice giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 66 publications
10
48
0
Order By: Relevance
“…These isotype-dependent therapeutic effects were specific to anti-CD40 rather than the BCL 1 model itself, as anti-CD20 (18B12) therapy demonstrated the opposite, classical, activatory FcgR-and mIgG2a mAb-dependent profile demonstrated in other models (Fig. 1H and data not shown) (13,16,24,26). It is notable that to produce a therapeutic effect in the BCL 1 model using direct targeting mAb such as anti-CD20 or anti-idiotype (data not shown), it is necessary to treat the mice at a very early stage (days 1-4) when the tumor burden is minimal and with large quantities of mAb (typically 200-250 ug).…”
Section: Therapeutic Activity Of Anti-cd40 Is Dependent Upon Isotypementioning
confidence: 97%
See 1 more Smart Citation
“…These isotype-dependent therapeutic effects were specific to anti-CD40 rather than the BCL 1 model itself, as anti-CD20 (18B12) therapy demonstrated the opposite, classical, activatory FcgR-and mIgG2a mAb-dependent profile demonstrated in other models (Fig. 1H and data not shown) (13,16,24,26). It is notable that to produce a therapeutic effect in the BCL 1 model using direct targeting mAb such as anti-CD20 or anti-idiotype (data not shown), it is necessary to treat the mice at a very early stage (days 1-4) when the tumor burden is minimal and with large quantities of mAb (typically 200-250 ug).…”
Section: Therapeutic Activity Of Anti-cd40 Is Dependent Upon Isotypementioning
confidence: 97%
“…Anti-mouse FcgRIIB (AT130-2) was produced in-house (23). Anti-mouse CD20 (18B12) mAb isotypes have been previously described (24). Endotoxin-free OVA (endoOVA) was from Profos (Regensburg, Germany).…”
Section: Abs and Reagentsmentioning
confidence: 99%
“…Based on the observations with B cell-depletion therapy, we revisited the role of B cells in atherosclerosis by depleting B lymphocytes using a mAb to mouse CD20 that has ameliorated murine thyroidits (13), lupus (14), and arthritis (15). We found that B cell depletion prevented the development and progression of atherosclerosis.…”
mentioning
confidence: 99%
“…The protective role of B cells in atherosclerosis has stimulated interest in developing a protective vaccine for atherosclerosis, targeted toward harnessing the protective B cell-derived IgM response to oxidized LDL (8). B cell depletion mediated by mAb to CD20 remits a wide variety of inflammatory diseases in humans (9)(10)(11)(12) and mice (13)(14)(15)(16). In humans, rituximab, a chimeric Ab to human CD20, has been approved for treating intractable rheumatoid arthritis, although its value for other inflammatory diseases, such as systemic lupus erythematosus (10,11) and multiple sclerosis (12), is currently being assessed.…”
mentioning
confidence: 99%
“…Accumulation of these cases is necessary to clarify whether the decreased in thyroid autoantibody levels by repeated rituximab monotherapy is associated with the improvement of disease state derived from Hashimoto's thyroiditis. resulted in diminished B lymphocyte and T lymphocyte infiltration of the thyroid, thereby inhibiting the development of spontaneous autoimmune thyroiditis [23]. In our present cases, thyroid autoantibody levels decreased after rituximab monotherapy.…”
Section: Discussionmentioning
confidence: 49%